PENERAPAN STRUKTUR PONDASI TITIK SEBAGAI PENGGANTI PONDASI BATU BATA DALAM UPAYA PENCAPAIAN BIAYA YANG LEBIH EKONOMIS (STUDI KASUS RUMAH JABATAN PUSKESMAS KUMBE KABUPATEN MERAUKE) - Biatma Syanjayanta; Hilarius Chandra Syanjayakusuma; Julvan Rifai Patiekom (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2018)
Merauke Regency is a coastal area with muddy soil conditions, Merauke district is a very rare area of sand and gravel material, because of these conditions the community and housing business actors use red brick as a foundation structure material for houses, especially simple housing. Meanwhile, generally red bricks have a non-structural function.In this study the author tries to plan and compare costs in terms of the design model of the continuous foundation structure of red bricks with a point structure design model, in order to achieve a safe, comfortable and economical design result.This research was conducted by direct observation (survey) to the research location, namely in the Kumbe health center, Malind district, Merauke district. In addition, the author also conducted a literature study on the standards of prices and wages in the related institutions, analyzed the prices of the plan drawings, concluded the results of the research so that it became an input for the government / related agencies and the community.From the results of this study, it can be concluded that there is a very significant price difference. The difference reaches Rp. 14,670,000.00, where the design of a continuous foundation with a total length of its foundation is 60,953 M1, the cost reaches Rp. 41,120,000.00. While the design of the point foundation with the same total length, the cost only reaches Rp. 26,450,000.00. Kata kunci : Struktur Pondasi Titik., Estimasi Teknis., Struktur Pondasi Menerus.